1992
DOI: 10.1128/aac.36.3.545
|View full text |Cite
|
Sign up to set email alerts
|

Duration of rifampin chemoprophylaxis for contacts of patients infected with Haemophilus influenzae type B

Abstract: Rifampin is recommended as a prophylactic treatment for intimate contacts of young children who develop invasive infections with Haemophilus influenzae type B (Hib). A 4-day course of rifampin (20 mg/kg of body weight per day, not to exceed 600 mg as a maximum single daily dose) is 95% effective in eradicating pharyngeal colonization with Hib, thus effectively reducing the risk of both associated patients and recurrent illness in index patients less than 2 years old. This study compares rates of eradication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Depending on its concentration, this antibiotic can have bacteriostatic or bactericidal effects. 34 Rifampicin can have bactericidal activity against slow and irregularly growing Mycobacterium tuberculosis organisms and it also plays a significant role in the treatment of methicillinresistant Staphylococcus aureus (MRSA), 35 Neisseria meningitidis, 36 N. gonorrheae, 37 Haemophilus inf luenza, 38 Listeria species, 39 Legionella pneumophila, 40 and Brucella species. 1 Mutations on the rpoB gene often occur under rifampicin stress.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Depending on its concentration, this antibiotic can have bacteriostatic or bactericidal effects. 34 Rifampicin can have bactericidal activity against slow and irregularly growing Mycobacterium tuberculosis organisms and it also plays a significant role in the treatment of methicillinresistant Staphylococcus aureus (MRSA), 35 Neisseria meningitidis, 36 N. gonorrheae, 37 Haemophilus inf luenza, 38 Listeria species, 39 Legionella pneumophila, 40 and Brucella species. 1 Mutations on the rpoB gene often occur under rifampicin stress.…”
Section: ■ Discussionmentioning
confidence: 99%
“…32,35e38,63e66 A lower dose of rifampicin at 10 mg/kg/ day for four days 37 or a shorter two-day course of 10 mg/ kg/day either daily 67 or twice daily 29 were less effective, possibly because of a lower peak antibiotic levels. 68 However, one prospective randomised controlled trial comparing a four-day course of rifampicin (20 mg/kg a day up to a maximum of 600 mg) with a two-day course at the same Table 3 Secondary attack rate among US household contacts within 30 days of hospitalisation of the index case. It was possible to combine studies on secondary attack rates in households because the chi-squared test for heterogeneity showed that the attack rates were not significantly different (p Z 0.4 for any Hib disease, p Z 1.0 for both the <2-year-old and <4/<5-year-old age groups; for Hib meningitis, p Z 0.6 for <2-year-old, p Z 0.9 for the <4/<5-year-old and p Z 0.10 for the >4-year-old age group).…”
Section: Risk Of Secondary Casesmentioning
confidence: 99%
“…32,[35][36][37][38][63][64][65][66] A lower dose of rifampicin at 10mg/kg/day for four days 37 or a shorter two-day course of 10mg/kg/day either daily 67 or twice daily 29 were less effective, possibly because of a lower peak antibiotic levels. 68 However, one prospective randomised controlled trial comparing a four-day course of rifampicin (20 mg/kg a day up to a maximum of 600 mg) with a two-day course at the same dose reported similar rates of clearance of Hib pharyngeal colonisation (94% vs. 92%) among family contacts, with identical 95% confidence intervals (73-99%), although this study was poorly powered, with only 18 and 24 participants in the two groups, respectively. Other antibiotics including cotrimoxazole, ampicillin, cefaclor and a single dose of ceftriaxone were less effective than rifampicin.…”
Section: Eradication Of Carriagementioning
confidence: 99%